Student learning independence to improve communication and collaboration skills in view of gender - Nurhayati; Bahtiar (Journal of Education and e-Learning Research, 2024)
This research aims to determine the differences and influence of independent learning on communication and collaboration skills. This research uses survey methods and a quantitative-descriptive approach. Data was obtained using a questionnaire with a Likert scale. The research subjects using random sampling techniques consisted of 33 female students and 82 female students in the Islamic religious education study program at UIN Datokarama Palu, Indonesia. The questionnaire contains 18 statements: 10 indicators of learning independence (LII), 3 indicators of communication skills (COM) and 5 indicators of collaboration skills (CLB). According to the results of data analysis using the Winsteps (Rasch model), male students have the best collaborative skills while female students are better at autonomous learning and the capacity to listen to information is the COM that is hardest to obtain. After applying one-way analysis of variance (ANOVA), a statistical significance of sig<0.05 was found indicating that male and female students exhibited distinct skill sets in the post hoc Games-Howell type follow-up test. The results show that for male and female students, learning independence is more dominant than communication and collaboration skills. The distinction lies in the fact that female students prefer communication skills while male students prefer collaboration skills. Further results obtained through the general linear model (GLM) test show that independent learning has an effect on communication skills (96.8%) and collaboration skills (93%). Finally, it can be stated that there is a positive relationship between learning independence and communication and collaboration skills.